Heat wave : a novel - Thayer, Nancy, 1943- (New York : Ballantine Books, 2011)
After her husband's sudden death from a heart attack and to keep her family in their beloved Nantucket home, Carley Winsted transforms her expensive, expansive house into a bed-and-breakfast . But complications arise: Carley's mother-in-law disapproves; a friend forces Carley to keep a secret that, if revealed, will undo families and friendships; and, her late husband's former law partner keeps showing up at the most unexpected times.
Keywords: Bed and breakfast accommodations -- Fiction; Widows -- Fiction; Family secrets -- Fiction; Nantucket Island (Mass.) -- Fiction